'Ware hawk - Norton, Andre (Atheneum, 1983)
Spurred on by a recurring dream, Tirtha accompanied by a falconer, embarks on a dangerous journey to her ancestral home, aware that she is bound by a spell to fulfill a mission whose purpose is unknown to her.